STUDENT LEARNING MOTIVATION OF PRAYER THROUGH IMAGE MEDIA - Islamiyah, I; Mujiburohman, M; Meti Fatimah (Institut Islam Mamba'ul 'Ulum Surakarta, 2023)
This study aims to determine the increase in learning motivation of class I students in semester II at MIN 3 Boyolali in prayer lessons through picture learning media. This study used classroom action research methods and used three cycles of action with the stages of planning/preliminary design, action, observation and reflection. The subjects of this study were class I MIN 3 Boyolali Academic Year 2022/2023. The data collection method uses 2 techniques, namely observation techniques and closed questionnaires. The data obtained were analyzed using a percentage, namely dividing the increase in the average score of learning motivation by the average score before giving action and then multiplying it by 100%. The results of data analysis showed that there was an increase in learning motivation in the high category, namely 58.3%. The increase can be explained as follows, namely that there is an average learning motivation score of 24.6 before the action, then it becomes 31.04 or an increase of 26.0% in cycle I, then it becomes 36 or an increase of 47.9% in cycle II, and becomes 39 or an increase of 58.3% in the third cycle. So it can be concluded that the action to increase learning motivation in class I MIN 3 Boyolali has been successful. With an increase in the average score of learning motivation after being given a minimum of 50% action. The actions are 1) Asking students to pay attention to the prayer movements in the media images; 2) Ask students to practice prayer movements together; 3) asking students to practice harmony between prayer movements and readings in groups guided by their respective group leaders.